Typologies of the Fiqh Conception in the Covid-19 Pandemic Era (Exploration on Religious Views and Attitudes of Kyai-in mosques of North Coast of Java) - Zaenurrosyid, Ahmad; Sholihah, Hidayatus; Shidiq, Ghofar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This study aims to analyze the dynamics of the fiqh conception of the kyai and their congregations in the act of worship in the mosque. The practice of worship during the Covid-19 pandemic shifted in patterns and choices of kyai schools of thought after the MUI fatwa, which issued regulation regarding the temporary abolition of Friday, Eid prayers, tarawih, and the use of masks, hand sanitizers, and social distance (distanced rows) in congregation of 5 daily prayers and religious activities in the mosque. This diversity is interesting to explore because these various conceptions of the acts of worship give negative impacts to intra-religious harmony. There are signs of socio-religious conflicst, distrust of certain community leaders, symptoms of disharmony, disbelieve in other parties in the public sphere and social media. This socio-religious dialectical context is encountered by the kyai, leaders and communities on the northern coast of Central Java, especially in Pati Regency and Semarang City. This is qualitative research using multi-disciplinary methods regarding normative analysis of Islamic law and socio-anthropology. Data was collected through interviews with kyai and community leaders, observation and documentation. Data validation was carried out through triangulation, as well as descriptive-qualitative analysis, through reduction, data presentation, and drawing conclusions. The findings of this study are as follows: first, the dynamics of a new conception of fiqh as a result of the Covid-19 pandemic amid various MUI and government policies through the implementation of health protocol. Second, four typical new conceptions of fiqh were found for kyai and the public during a pandemic. The diversity of this community typology can be seen from their worship behavior and religious actions. Typical of the first group is ‘normative’ whose written texts are understood in literal sence about the pandemic jurisprudence and are very strict about implementing health protocol. The second is the ‘moderate group’ who is flexible in conceptualizing the fiqh of pandemic and carrying out health protocol. Third, there are ‘liberative-ignore’ groups who are liberal in understanding fiqh during the pandemic, and they do not pay much attention to the health protocol. Typical of the fourth group, the ‘skeptics’ who do not believe in the presence of the covid-19 pandemic, even among this group there are those who think that covid is just a power politics engineering.